Education Model Study of Religious Nationalist Character Construction in Pesantren Pasuruan - Achmad Yusuf; Mochamad Hasyim; Askhabul Kirom (Ta'dib, 2024)
Pesantren has an important role in developing the education world and providing solutions to current educational problems. This study aims to examine the campursari educational model and its process in shaping nationalist-religious character in Pesantren. The study uses a descriptive method with purposive sampling and interactive model analysis. The results show that Pesantren Ngalah Pasuruan has a campursari educational model that integrates formal, non-formal, and informal education. The campursari educational process in this pesantren involves the integration of religious and cultural values, the development of creativity and critical thinking, and the empowerment of local culture. The campursari model in Pesantren includes the integration of religious education with local cultural values, a curriculum with a campursari approach, the development of inclusive materials, the empowerment of local culture, and the strengthening of religious values through interfaith activities. The implications of this study are; enriching the understanding of campursari education and its implications in developing inclusive curricula, strengthening interfaith cooperation, and enhancing the role of Pesantren education in developing similar models in other educational institutions, particularly Islamic boarding schools, to improve the quality of education and shape strong nationalist-religious characters in students.